Influence of Some Rhizobium Strains on Chickpea: Nodulation, dry matter yield and Nitrogen uptake - Solaiman, ARM; Talukder, MS; Rabbani, MG (Bangladesh Journal of Microbiology, 2011)
Four strains of Rhizobium were isolated from chickpea (Cicer arietinum) to characterize and observe the effectiveness on host legumes. In a laboratory study, Rhizobium strains showed standard pattern of reactions in respect of growth rate, colony characteristics and acid/alkali production on different growth media. The effect of Rhizobium inoculation on nodulation, growth and nitrogen fixation of chickpea was assessed by pot experiment on clay loam soil. Inoculation treatments comprised of Rhizobium strains CR1, CR2, CR3 and CR4. Rhizobium inoculation had significant positive effects on nodulation, growth and nitrogen fixation of the crop. Among the Rhizobium strains CR2 and CR3 performed better than CR1 and CR4 at 50% flowering stage of the crop. There were high positive correlations among the number and dry weight of nodules, N content and N uptake by shoot of chickpea. Keywords : Rhizobium; Nodulation; Growth; Nitrogen fixation; Chickpea DOI: http://dx.doi.org/10.3329/bjm.v27i2.9174 BJM 2010; 27(2): 61-64